Implementasi Kurikulum 2013 Revisi 2016 Pada Pembelajaran Menulis Teks Anekdot - Rasyid Manshur; Sarwiji Suwandi; Suyitno Suyitno (Jurusan Tadris Bahasa Indonesia, 2018)
The objectives of this research are to describe and explain (1) the process of writing anecdote text based on the 2013 Curriculum and its 2016 revision conducted by the teachers of Indonesia Language subjects in class X SMK Negeri 1 Gondang Sragen, (2) the existing obstacles in the process of writing anecdote text of the 2013 Curriculum and its 2016 revision in class X SMK Negeri 1 Gondang Sragen, and 3) the teachersâ€™ efforts to overcome the obstacles encountered in the process of writing anecdotal text based on the 2013 Curriculum and its 2016 revision in class X SMK Negeri 1 Gondang Sragen. This qualitative research used a case study approach. The data sources in this research were events (the process of writing anecdote text), informants (teachers and students), and documents (the syllabus and lesson plan). The results show that the implementation of learning to write anecdotal text based on the 2013 Curriculum and its 2016 revision needs a more in-depth assessment in order to improve planning, implementation, and assessment. It is also based on the encountered obstacles occurred in the learning processes. Thus, the implementation of the 2013 Curriculum and its 2016 revision is in line with the concepts and regulations of the government. This is also implied for the achievement of national education objectives.Â Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan pembelajaran menulis teks anekdot Kurikulum 2013 revisi 2016 yang dilakukan oleh guru mata pelajaran bahasa Indonesia di kelas X SMK Negeri 1 Gondang Kabupaten Sragen, kendala-kendala, serta upaya-upaya yang dilakukan oleh guru. Penelitian kualitatif ini menggunakan pendekatan studi kasus. Sumber data penelitian ini adalah peristiwa pembelajaran menulis teks anekdot, informan (guru dan siswa), dan dokumen (silabus dan RPP). Hasil penelitian menyimpulkan bahwa implementasi Kurikulum 2013 revisi 2016 pada pembelajaran menulis teks anekdot masih membutuhkan pengkajian lebih mendalam supaya dapat meningkatkan perbaikan implementasi, baik dari perencanaan, pelaksanaan, maupun penilaian mengingat masih sering adanya kendala-kendala yang dijumpai dalam pembelajaran. Dengan demikian, implementasi Kurikulum 2013 revisi 2016 yang sejalan dan selarasdengan tata konsep dan peraturan yang sudah ditentukan pemerintah dapat terwujud, juga berimplikasi pada ketercapaian tujuan pendidikan nasional.